KERUSAKAN ALAM AKIBAT TAMBANG EMAS RAKYAT DI NAGARI KOTO BARU KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG DALAM KARYA SENI GRAFIS TEKNIK CETAK TINGGI - SESMIATI, Drs. Ariusmedi, M.Sn, Drs. Irwan, M.Sn (Universitas Negeri Padang, 2015)
The utilization of natural resources in gold-mining business can increase prosperity in community, but it can bring natural destruction and social problems. This typography is purposed to visualize the effect of gold-mining in Nagari Koto Baru IV Nagari district Sijunjung regency in order to give comprehension of negative impact that is happen in the environment surrounding because of gold-mining activities. The typography consists of ten graphic art-works which is picturing the environment before and after the activities of gold-mining where art becomes its milestone. There is a suggestion that this research can be an input for another artists to promote similar theme and also an inspiration for other students to promote this problems to become a concept in their research because there is still many aspect that are not covered in this research.